Implementasi Kebijakan Bantuan Langsung Tunai dalam Pengentasan Kemiskinan di Kelurahaan Moodu Kecamatan Kota Timur Kota Gorontalo - Ibel Stefani Putri; Yacob Noho Nani; Romy Tantu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This aims to examine and analyze the implementation of the cash transfer assistance policy in efforts to alleviate poverty in Moodu Urban Village, Kota Timur Subdistrict, Gorontalo City. This research employed a qualitative method. The findings indicate that the effectiveness of the policy implementation has not yet been optimal due to several influencing factors: (1) policy standards and target groups have not been fully accurate; (2) available resources, both in terms of the number of implementing personnel and supporting infrastructure, remain very limited; (3) inter-organizational communication and activity reinforcement are less effective; (4) the characteristics of implementing agents reveal that some officers do not yet fully understand the procedures and mechanisms for distributing cash transfer assistance; (5) the economic, social, and political environment of the Moodu community, which is predominantly engaged in the informal sector, presents additional challenges in ensuring program effectiveness; and (6) the attitudes of implementers, in the absence of continuous guidance and periodic supervision, increase the potential for administrative errors and inaccurate distribution.